New data on familial hypercholesterolaemia and acute coronary syndromes: The promise of PCSK9 monoclonal antibodies in the light of recent clinical trials. (July 2017) - Ellis, Katrina L; Pang, Jing; Schultz, Carl J; Watts, Gerald F
Background: Familial hypercholesterolaemia (FH) is an autosomal dominant disorder characterised by substantially elevated low-density lipoprotein (LDL) cholesterol. Although affecting approximately one in 250 individuals worldwide, FH is currently underreported and a greater awareness of this condition is required. Opportunistic screening for FH in acute coronary syndrome patients offers utility for identifying previously undiagnosed individuals and for initiating treatment. Methods: The purpose of this commentary is to provide a brief update on recent data investigating several key aspects of FH in patients with acute coronary syndromes, including prevalence, risk of coronary artery disease, molecular diagnosis, cardiac imaging, as well as the efficacy of PCSK9 inhibition. Results: FH is relatively common among patients with coronary artery disease and is associated with a considerably increased risk of premature and recurrent cardiovascular events. Computed tomographic coronary angiography may be useful for identifying high-risk FH individuals. FH patients with a pathogenic mutation have a greater risk of the same LDL cholesterol than individuals without a mutation. PCSK9 monoclonal antibodies significantly lower LDL cholesterol in heterozygous and homozygous FH patients, with a greater attainment of LDL cholesterol targets, and can reduce the need for lipoprotein apheresis. Conclusions: These data support the opportunistic screening for FH at the time of angiography or an acute coronary syndrome, followed by cascade testing of relatives of index cases. PCSK9 monoclonal antibodies are an important therapeutic advance for safely inhibiting the progression of atherosclerotic burden in FH, as supported by the most recent clinical endpoint trials.